2022
DOI: 10.1007/s13385-022-00307-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient use of data for LSTM mortality forecasting

Abstract: We consider a simple long short-term memory (LSTM) neural network extension of the Poisson Lee-Carter model, with a particular focus on different procedures for how to use training data efficiently, combined with ensembling to stabilise the predictive performance. We compare the standard approach of withholding the last fraction of observations for validation, with two other approaches: sampling a fraction of observations randomly in time; and splitting the population into two parts by sampling individual life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…More recently, Lindholm and Palmborg (2022) discussed the procedures to efficiently use training data in mortality forecasting when applying an LSTM-based Poisson LC method. Marino et al (2022) further confirmed that an LSTM model can improve the predictive power of the classical LC method by providing a rigorous analysis of the prediction interval for their so-called LC-LSTM model.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Lindholm and Palmborg (2022) discussed the procedures to efficiently use training data in mortality forecasting when applying an LSTM-based Poisson LC method. Marino et al (2022) further confirmed that an LSTM model can improve the predictive power of the classical LC method by providing a rigorous analysis of the prediction interval for their so-called LC-LSTM model.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches that use machine learning techniques for forecasting mortality rates can be found in e.g. Richman and Wuthrich (2019); Richman and Wüthrich (2021); Perla et al (2021) that consider various types of Gaussian recurrent neural network structures, Nigri et al (2019); Marino and Levantesi (2020); Lindholm and Palmborg (2022) that consider univariate LSTM neural network, both with and without a Poisson population assumption, and Deprez et al (2017) that consider tree-based techniques.…”
Section: Introductionmentioning
confidence: 99%